Acute Aortic Thrombosis Related to Adjuvant Capecitabine-Oxaliplatin in a Chinese Patient with Resected Adenocarcinoma of Sigmoid Colon - Wong, Henry C. Y.; Lim, Fiona M. Y.; Cheng, Ashley C. K. (Archives of Clinical and Medical Case Reports, 2019)
Aortic thrombosis is a rare disease entity which has been reported to be related to malignancy and chemotherapeutic agents. Here we present the first case in literature about a colon cancer patient with well-controlled vascular risk factors who developed acute aortic thrombosis after the first cycle of adjuvant chemotherapy with capecitabine-oxaliplatin. Risk factors and causal relationship between systemic anti-cancer agents and this condition are reviewed and discussed.